O narrador e a narrativa gráfica de Lourenço Mutarelli em Nada me Faltará - Sgambatti Júnior, Milton (2013)
The main objective of this research is the study of the book Nada me Faltará of Lourenco Mutarelli in view the absence of a narrator and the way the narrative installs itself at the intersection between the novel and the graphic novel, significant fact arising to an author of comics. To conduct these reflections we propose as a hypothesis nuclear the fact that this is a novel that, to be write just for dialogues, stands on the threshold between the novel and the graphic novel, creating a sort of sequential narrative art from the present, in experience of the here and now of the relation it establishes between the text and the reader. As grounds for this research are reflections about narrator and about the concept of history by Walter Benjamin, and the critical positioning of Will Eisner on the narrative art of the graphic novel. The analysis results highlight how critical Nada me Faltará is located around for new narrative format made from residues and forgetting in whose void spaces and reticence signs, materialized by graphic sign ... are inscribed actions of a narrator in state of an output, typical of contemporary times